Consciousness: a neural capacity for objectivity, especially pronounced in humans - Dijker, Anton J. (Frontiers in Psychology, 2014)
Consciousness either tends to be viewed as subjective experience of sensations and feelings, or as perception and internal representation of objects. This paper argues that neither view sufficiently acknowledges that consciousness may refer to the brain’s most adaptive property: Its capacity to produce states of objectivity. It is proposed that this capacity relies on multiple sensorimotor networks for internally representing objects and their properties in terms of expectancies, as well as on motivational and motor mechanisms involved in exploration, play, and care for vulnerable living and nonliving objects. States of objectivity are associated with a very special phenomenal aspect; the experience that subjective aspects are absent and one is “just looking” at the world as it really is and can be. However, these states are normally closely preceded and followed by (and tend to be combined or fused with) sensations and feelings which are caused by activation of sensory and motivational mechanisms. A capacity for objectivity may have evolved in different species and can be conceived as a common basis for other elusive psychological properties such as intelligence, conscience, and aesthetic experience; all three linked to crucial behaviors in human evolution such as tool making, cooperation, and art. The brain’s pervasive tendency to objectify may be responsible for wrongly equating consciousness with feelings and wrongly opposing it to well-learned or habitual (“unconscious”) patterns of perception and behavior.